IMPLEMENTASI PENGEMBANGAN APARATUR MELALUI LEARNING MANAGEMENT SYSTEM DI KOTA TANGERANG (Studi di Badan Kepegawaian dan Pengembangan SDM Kota Tangerang) - Oktavioni, Dewi; Mulyadi, Edi; Eliadi Hardian, Dafyar (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
In Law Number 5 of 2014 concerning State Civil Apparatus, ASN Employees must have a profession and ASN management based on a merit system that emphasizes employee qualifications, competencies, and performance. The government's seriousness in overcoming the problem of apparatus development is proven through PP No. 17 of 2020 concerning Civil Servant Management, which explains that all civil servants in 1 year have the opportunity for at least 20 hours of lessons to develop their competencies. The entry of the 4.0 era industry is the rapid development of technology in the world. Like it or not, of course this has an impact on technological progress in Indonesia. Starting from the Covid-19 pandemic and for the effectiveness of apparatus development activities, a policy was issued by the Tangerang City Government regarding apparatus development through the Learning Management System. However, seeing the conditions of virtual learning which have obstacles in their implementation, it creates a problem related to the process of apparatus development in the Tangerang City Government. Objective: Based on the background, the author compiled this study with the aim of knowing how the implementation of Apparatus Development through Learning Management System in Tangerang City, knowing what supporting and inhibiting factors are in the implementation of apparatus development through LMS in Tangerang City. Method: The research method uses a descriptive qualitative method with data sources in the form of interview results, observations and supporting documents and proven by documentation. Results/Findings: The results of the study indicate that in the development of apparatus through LMS in Tangerang City has been running according to the objectives, but there are still technical obstacles, namely the transition conditions from classical learning to virtual learning, such as the condition of LMS management human resources which are still lacking and learning support features have not been optimally used, as well as the lack of active role of the apparatus for self-learning. Conclusions and Suggestions: The addition of technical LMS management human resources such as operators, the need for LMS management training for BKPSDM Diklat HR and the need for Socialization to Tangerang City Government apparatus regarding apparatus development through LMS (self-learning) Keywords: Implementation, apparatus development, LMS